Förster Resonance Energy Transfer across interpolymer complexes of poly(acrylic acid) and poly(acrylamide). (11th August 2017) - Swift, Thomas; Paul, Natalie; Swanson, Linda; Katsikogianni, Maria; Rimmer, Stephen
Abstract: Interpolymer complexes of homopolymer macromolecules are often described as 'laddered' or 'ribbon' type structures. The proposition of the existence of these ladder structures seems to us not reasonable and here we examine this hypothesis. To address this we have used polymers enabled for Förster Energy Transfer (FRET). Chromophores bound to a macromolecular backbone can transfer energy across short distances via FRET. The close binding of poly(acrylamide) and poly(acrylic acid) interpolymer complex formation at low pH forms a structure compact enough for significant energy transfer to occur between different chains containing naphthalene and anthracene labels. In the context of the proposition that ladder polymers can form it was surprising that the distance between labels on the same polymer back-bone was equivalent regardless of whether the polymer was complexed or not. The data indicated that the bicomponent structure may be more compact than previously supposed: I.e. the complexes are not ladders composed of extended chains. This evidence suggests formation not of ordered 'ladder' systems but colloidal 'co-globules'. Graphical abstract: